The acceptance of advanced carbohydrate counting booklet among diabetes patient in Hospital Putrajaya / Nurul Iman Hafizah Adanan - Adanan, Nurul Iman Hafizah (2016)
Incorporation of carbohydrate counting in the management of type I diabetes allows a more flexible food choices with no metabolic effects and other harmful health consequences. The purpose of carbohydrate counting is to match the amount of carbohydrate that the patient is going to take with the insulin dosing. This study was done to evaluate the acceptance of advanced carbohydrate counting booklet among patients with type I diabetes. This study was an experimental study, using pre- and post-test study design with an interval of one week to determine whether the knowledge level among the subjects. This study have found out that the advanced carbohydrate counting booklet was accepted among diabetes patients as subjects agreed that the booklet was understandable and actionable. The booklet scored above 70%, which were 86.33 ± 16.76% for understand ability domain and 88.78 ± 17.31% for action ability. This study also found that there was no significant difference between the level of knowledge of subjects between pre- and post-test with p value of 0.052 (p>0.05). Lastly, result also have shown that there was a weak, not significant correlation between the acceptance of advanced carbohydrate booklet and the knowledge level of subjects. As a conclusion, the advanced carbohydrate counting booklet was accepted among diabetes patients. However, there was no significant difference between the knowledge levels on advanced carbohydrate counting before and after the booklet was distributed among subjects.